2001
DOI: 10.1515/jpem.2001.14.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Birth in Children (0-14 Years) with Type 1 Diabetes Mellitus in Slovenia

Abstract: The aim of this study was to find out whether there is seasonality of month of birth of children with diabetes in Slovenia and if so whether it differs from that of the general population. A cohort of 849 children and adolescents (0-14 years) with type 1 diabetes mellitus born between 1956 and 1998 were included in the study. Monthly and seasonal patterns of birth of the patients with diabetes were compared with the pattern of normal live births (n = 1,345,921) and the pattern of disease onset. Statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The trend in HbA 1c variation is consistent with seasonal variation of type 1 diabetes incidence [17, 18]. An inverse correlation with ultraviolet irradiance and diagnosis of type 1 diabetes has been observed in Newfoundland, Canada [19].…”
Section: Discussionmentioning
confidence: 57%
“…The trend in HbA 1c variation is consistent with seasonal variation of type 1 diabetes incidence [17, 18]. An inverse correlation with ultraviolet irradiance and diagnosis of type 1 diabetes has been observed in Newfoundland, Canada [19].…”
Section: Discussionmentioning
confidence: 57%
“…Consistent results were found in Ukraine (highest variability in western Europe) [81], Sweden [82], Greece [83], Ireland (significant in boys only) [84], Slovenia [85], Germany [86], The Netherlands [87], Britain [88], New Zealand [89], and Sardinia [90]. However, a multicenter cohort study in Europe found no seasonal variations [91].…”
Section: Seasonal Variability In the Incidence Of T1dmmentioning
confidence: 62%
“…The discrepancy was not clear, but it might be explained by the differential effects of climate and temperature on various geographical areas. Seasonal birth pattern was reported in a number of neuropsychiatric disorders, such as Parkinson’s disease, schizophrenia, bipolar affective disorder and autoimmune disorders such as type 1 diabetes mellitus 4042. It indicated that the seasonal variations of environmental factors, such as nutrition, sunlight, toxins, infectious agents and temperatures, may well be involved in the aetiology of these diseases during early fetal development in subjects with a genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%